Apgar Score Components at 5 Minutes: Risks and Prediction of Neonatal Mortality. Issue 4 (11th May 2017) - Cnattingius, Sven; Norman, Mikael; Granath, Fredrik; Petersson, Gunnar; Stephansson, Olof; Frisell, Thomas
Abstract: Background: The Apgar score consists of five components: heart rate, respiratory effort, muscle tone, reflex irritability, and colour. Although the Apgar score has been used for 60 years, the specific contribution of the Apgar score components with respect to risks and prediction of neonatal mortality remains unknown. Likewise, the value of reduced scores (including less than five Apgar score components) has rarely been investigated. Methods: In a population‐based cohort study of 148 765 liveborn singleton infants in Sweden 2008–2013, we investigated components of Apgar score at 5 min with respect to relative risks and prediction (using ROC curves, sensitivity, and positive predictive values) of neonatal mortality. Results: Reduced values (0–1) of heart rate, respiratory effort, and colour were independently associated with increased relative risks of neonatal mortality. For the full Apgar score, the sensitivity and positive predictive values of neonatal mortality (cut‐off ≤3) were by gestational age: ≤31 weeks: 56.1% and 49.2%; 32–36 weeks: 25.0% and 18.2%; and ≥37 weeks: 35.2% and 9.3%, respectively. When only heart rate and respiratory effort were considered (range 0–4; cut‐off ≤2), corresponding values were 66.7% and 34.9%; 37.5% and 13.0%; and 46.3% and 7.6%, respectively. Conclusions: A reduced Apgar score has generally the same predictability of neonatal mortality as the full Apgar score. The full Apgar score or reduced scores may be better predictors of neonatal mortality in very preterm infants (≤31 weeks) than in infants with longer gestations.